Extension of charge-state-distribution calculations for ion-solid collisions towards low velocities and many-electron ions - Lamour, E.; Fainstein, Pablo Daniel; Galassi, Mariel Elisa; Prigent, C.; Ramirez, C. A.; Rivarola, Roberto Daniel; Rozet, J. P.; Trassinelli, M.; Vernhet, D. (American Physical Society, 2015)
Fil: Lamour, E.. Centre National de la Recherche Scientifique; Francia. Universite de Paris; Francia